PENGARUH MODAL MANUSIA TERHADAP UPAH PEKERJA PADA SEKTOR JASA MONTIR MOTOR DI PALEMBANG - Theodorus William Siahaan (AKUNTABILITAS, 2014)
This study describes the services of motor mechanic workers who work in non-authorized workshops / individuals who have at least 1 motor mechanic spread in Palembang, especially in 16 sub-districts in Palembang. The data used in this study is the primary data obtained from the survey by conducting longitudinal interviews through prepared cues. Variables used in this study are education, training, work experience and working hours. The parameter parameters of the model are calculated by the OLS method with the help of the Eviews 7 program. Furthermore, an Econometrics Criteria Test is required. The results obtained are that the educational variables, ker ka kercha experience each significant effect on the wage pointing while the variable training is not significant to the wage pointers on motor mechanic services in Palembang.